Alan Tower Waterman papers - Waterman, Alan Tower, 1892-1967.
Correspondence, diary notes (1947-1963), speeches, articles, travel itineraries, subject file, biographical material, and other papers chiefly relating to Waterman's activities as an administrator of scientific research organizations including his years as deputy chief of the U.S. Office of Naval Research (1946-1951) and as director of the U.S. National Science Foundation (1951-1963). Includes material concerning the foundation's role in fostering U.S. participation in the International Geophysical Year, 1957-1958, and the first successful launching of an American space satellite. Also documents his teaching career as a professor of physics at Yale University (1919-1942), experience as chief reader for the College Entrance Examination Board, and association with such organizations as the American Association for the Advancement of Science, Center for Advanced Study in the Behavioral Sciences (Stanford, Calif.), and the Cosmos Club (Washington, D.C.).
Individuals represented include Detlev W. Bronk, Vannevar Bush, K.T. Compton, James Bryant Conant, Lee A. Dubridge, George Gamow, Willard Frank Libby, Sir Bernard Lovell, Margaret Mead, J. Robert Oppenheimer, Harlow Shapley, Norbert Wiener, and Jerrold Reinach Zacharias.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Physicist and science administrator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bronk, Detlev W. -- 1897-1975.; Bush, Vannevar, -- 1890-1974.; Compton, K. T. -- 1887-1954.; Conant, James Bryant, -- 1893-1978.; DuBridge, Lee A. -- 1901-1994.; Gamow, George, -- 1904-1968.; Libby, Willard F; Lovell, Bernard, -- 1913-2012.; Mead, Margaret, -- 1901-1978.; Oppenheimer, J. Robert, -- 1904-1967.; Shapley, Harlow, -- 1885-1972.; Wiener, Norbert, -- 1894-1964.; Zacharias, Jerrold Reinach, -- 1905-1986.; American Association for the Advancement of Science; Center for Advanced Study in the Behavioral Sciences (Stanford, Calif.); College Entrance Examination Board; Cosmos Club (Washington, D.C.); National Science Foundation (U.S.); United States. -- Office of Naval Research; Yale University -- Faculty; Artificial satellites; International Geophysical Year, 1957-1958.; Physics -- Study and teaching; Research; Science -- Societies, etc; Administrators; Physicists